Makna Simbolik “Popene’e” Pada Prosesi Pernikahan Etnik Tialo di Kabupaten Parigi Moutong: Kajian Semiotik - Arfan Fauzan; Yunidar Yunidar; Sukma Sukma (Badan Pengembangan dan Pembinaan Bahasa, 2025)
The purpose of this research is to describe the forms of symbolic meaning and the functions of symbolic meaning in the